The Effectiveness Of School Intervention Program On Tobacco Use, Alcohol And Use Among Form Two Students in Four Secondary Schools In Kota Bharu, Kelantan. - Romli , Jaidon (2001)
To assess the knowledge, attitudes, skills and practices in relation to tobacco use, alcohol and drug use among Fonn Two students in four secondary school in Kota Bharu, Kelantan and to assess the effectiveness of school intervention programs that use students as a peer group to educate their colleague.